An In Silico Evaluation of Flavonoids in Allium sp. as a Potent Anti-Acute Myeloid Leukemia (AML) Through FLT3 Inhibition - Galuh Nafisah Diva; I Gusti Ngurah Agung Wiwekananda; Naila Salsabila Mawardi; Puspa Andhia Kemala Sari; Safira Aulia Rahma; Ichda Arini Dinana; Nia Kurniawan; Fatchiyah Fatchiyah (JSMARTech, 2022)
Acute Myeloid Leukemia (AML) is the most common leukemia caused by genetic abnormalities that affect the hematological proliferation and induce incomplete differentiation of myeloid cells in the peripheral blood and bone marrow. AML involving FLT3 gene mutation results in overexpression of FLT3 receptors. This study intended to predict the interaction between the FLT3 receptor in AML with flavonoids found in Allium sp. by a molecular docking method. Several 3D molecule structures of the highest flavonoids from Allium sp., including quercetin, kaempferol, isorhamnetin, myricetin, fisetin, morin, isoquercetin, quercitrin, spiraeoside, and quercetin-3,4-O-diglucoside were obtained from the PubChem database. Meanwhile, the FLT3 receptor complex with gilteritinib 3D structure was obtained from the RCSB PDB database. All compound properties were assessed using Swiss-ADME. FLT3 receptor prepared using Discovery Studio 2019. Meanwhile, all flavonoids' energy as ligands is minimized using PyRx 0.8 software. The specific docking was performed using Autodock Vina integrated with PyRyx v 0.8 software and visualized using Discovery Studio 2019, and several parameters of the docking data were analyzed. All flavonoids show favorable drug-likeness and pharmacokinetics properties apart from four quercetin derivatives. Meanwhile, the molecular docking result shows that Quercetin, kaempferol, isoquercetin, quercitrin, spiraeoside, and quercetin-3,4-O-diglucoside have inhibitory potential against FLT3 receptors because they share several same binding sites as control. They also have a fairly high binding affinity compared to the other compounds tested. Molecular dynamic simulation result demonstrates a considerably stable complex. It is estimated that quercetin and kaempferol from Allium sp. have the potential to be used as therapeutic drugs against AML.